Cloud-Based Enhanced Storage System Using Android Technology - Malathy, Batumalay; Krieshaanthiny, Nagasvarao; Chitra, Batumalai (INTI International University, 2021)
Cloud storage is a secure-oriented aspect for users. It provides on-demand service to the user, where users can connect to a cloud through network to store user’s data in the cloud. In a frequently connected world, users obtain personal or shared data stored in the cloud such as Dropbox, Google Drive and Microsoft One Drive with the various gadget. This shows the popularity of cloud storage being used among users. This project aims to integrate enhance features in cloud storage which can be more adaptability for users. This proposed system contains the mobile application and web application that implemented using Android Studio for mobile app, PHP for a web app and it will be stored in the cloud via Google Cloud. This system also provides basic characteristics such as delete file, attach documents and file recovery. The enhancement characteristics are QR Code and chatbot where, QR code used to scan into a web for website and chatbot allow the users to communicate within the same application. The author has chosen the questionnaire and case study as fact-finding method for proposed system.